A review of the DTaP-IPV-HB-PRP-T Hexavalent vaccine in pediatric patients - Andrew Dakin; Ray Borrow; Peter D. Arkwright (Expert Review of Vaccines, 2023)
Introduction Hexaxim is a hexavalent vaccine approved as primary and booster vaccination in infants 6 weeks and older, protecting against diphtheria, tetanus, pertussis, poliomyelitis, hepatitis B and Haemophilus influenzae type b. Areas Covered To evaluate the immunogenicity and reactogenicity (safety) of Hexaxim (Hexyon, Hexacima) in primary and booster vaccine schedules; long-term antibody persistence; concomitant use with other childhood vaccines and use in immunocompromised infants. Hexaxim was found to be noninferior to other licensed hexavalent vaccines, being highly immunogenic for all toxoids/antigens and with an acceptable safety profile. It can be administered concomitantly with other childhood vaccines. Hexaxim can be given as a booster for infants primed with Infanrix Hexa and given in a pentavalent-hexavalent-pentavalent series. Hexaxim elicits a similar immune response and safety profile in human immunodeficiency virus (HIV) positive infants. It has the benefit of being a ready-to-use liquid formulation, minimizing dosage errors and preparation time. Expert Opinion Hexaxim has an acceptable safety profile and provides immunity against all six targeted diseases. It is an acceptable alternative to other hexavalent vaccines on the market. Further studies are required on the use of immunocompromised patients as well as the antibody persistence of each of the vaccine components.